The role of inflammatory movies in shaping Islamophobia and destination animosity - Masroor, Zahid; Arora, Nilesh (Taylor and Francis Ltd., 2024)
In an increasingly globalised world, tourism is a powerful medium for cultural exchange and understanding. However, it is also a realm where negative stereotypes can manifest. Movies with inflammatory content can create infractions and evoke emotions which can manifest towards cultures, religions and traditions. Although the effects of storylines on destinations have been widely studied, the studies examining the effects of inflammatory movies towards destinations remain scant. Our study explains the formation of Islamophobia via imitation and modelling by using media dependency theory as a theoretical template. We used multi-group analysis to study the effects of inflammatory movie on two groups based on exposure to the movie. Our results revealed higher levels of Islamophobia among participants who were exposed to an inflammatory movie titled ‘The Kashmir Files.’ The study enriches media dependency theory and provides insights to destination stakeholders about the effects of inflammatory storylines towards destinations.